The internalization of nationalistic values in the development of civic character among students at the Munzalam Mubaroka Islamic Boarding School - Titin Fitriani; Sri Rahayu (Educenter : Jurnal Ilmiah Pendidikan, 2026)
This study aims to analyze the process of internalizing nationalist values, identify supporting and inhibiting factors, and examine the civic character of students at the Munzalam Mubaroka Islamic Boarding School. This research employs a qualitative descriptive approach with data collected through observation, in-depth interviews, and documentation. Data analysis was conducted through data reduction, data display, and conclusion drawing, supported by validity testing using triangulation techniques. The findings reveal that the internalization of nationalist values is carried out systematically through habituation, role modeling, and various religious and social activities within the boarding school environment. Supporting factors include students’ internal motivation, the exemplary role of teachers and dormitory administrators, and community support, while inhibiting factors consist of low nationalism awareness among some students, external social influences, and limited facilities. Furthermore, the internalization process contributes to the development of students’ civic character, reflected in attitudes of tolerance, discipline, responsibility, social awareness, and patriotism. The study highlights that the integration of religious and national values in pesantren education plays a significant role in shaping students into responsible citizens who maintain both their religious identity and national commitment.